THE ROLE OF ANALYZING THE FINANCIAL SITUATION OF INDUSTRIAL ENTERPRISES IN THE MARKET ECONOMY - Mamadalieva Matlyuba Tajidinovna (Zeta Repository, 2023)
The article examines the theoretical aspects of financial stability of enterprises and systematizes indicators of financial stability based on the specific characteristics of industrial enterprises. Also, the state of financial stability of industrial enterprises was evaluated and analyzed. Based on the results of the analysis, a scientific proposal and practical recommendations aimed at ensuring the financial stability of industrial enterprises were developed.